2018
DOI: 10.1007/s00726-018-2579-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing amino-acid biosignatures amongst individuals with schizophrenia: a case–control study

Abstract: Amino acids and derivatives participate in the biosynthesis and downstream effects of numerous neurotransmitters. Variations in specific amino acids have been implicated in the pathophysiology of schizophrenia. Herein, we sought to compare levels of amino acids and derivatives between subjects with schizophrenia and healthy controls (HC). Two hundred and eight subjects with Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition criteria (DSM-IV)-defined schizophrenia and 175 age- and sex-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 57 publications
4
24
0
5
Order By: Relevance
“…However, although our patients exhibited state and trait immune activation, the GTP-CH1 pathway did not differentiate patients from controls (except for nitrite) and the IDO pathway appeared overall downregulated in patients vs. controls. Although this finding contradicts our original hypothesis of immune-activated IDO upregulation, it is in line with results from two recent amino-acid profiling studies (one cross-sectional study in 208 first episode psychosis patients and one 7month follow-up study in 38 schizophrenia patients) in which tryptophan and kynurenine were decreased in participants with schizophrenia vs. controls (26,27).…”
Section: Trait and State Markers Of Psychotic Illnesssupporting
confidence: 63%
“…However, although our patients exhibited state and trait immune activation, the GTP-CH1 pathway did not differentiate patients from controls (except for nitrite) and the IDO pathway appeared overall downregulated in patients vs. controls. Although this finding contradicts our original hypothesis of immune-activated IDO upregulation, it is in line with results from two recent amino-acid profiling studies (one cross-sectional study in 208 first episode psychosis patients and one 7month follow-up study in 38 schizophrenia patients) in which tryptophan and kynurenine were decreased in participants with schizophrenia vs. controls (26,27).…”
Section: Trait and State Markers Of Psychotic Illnesssupporting
confidence: 63%
“…N-acetyl group metabolites are the acetylated variant of amino acids and organic acids, which are a general class of endogenous compounds characterized by a conjugated system consisting of an acetyl group and nitrogen moiety. Two of our previous studies have already confirmed that some of the amino acids and organic acids might be associated with the pathogenesis and progression of schizophrenia (Cao et al, 2018a;Cao et al, 2018b). Also, Nacetyl-glucosamine has been shown to act as a nutrient sensor and mediator of insulin resistance (Wells et al, 2003).…”
mentioning
confidence: 85%
“…Cao (2018) áûëî ïîêàçàíî ïîâûøåíèå êîíöåíòðàöèé ñûâîðîòî÷íîãî öèñòåèíà, γ-àìèíîìàñëÿíîé êèñëîòû, ãëóòàìèíà è ñàðêîçèíà è ñíèaeåíèå àðãèíèíà, L-îðíèòèíà, òðåîíèíà, òàóðèíà, òðèïòîôàíà, ìåòèëöèñòåèíà è êèíóðåíèíà â ãðóïïå áîëüíûõ øèçîôðåíèåé ñ êîððåêòèðîâêîé íà ïîë, âîçðàñò è èíäåêñ ìàññû òåëà ïî ñðàâíåíèþ ñî çäîðîâûìè ëèöàìè. Êðîìå òîãî, ó ïàöèåíòîâ ñ ïåðâûì ýïèçîäîì øèçîôðåíèè â îòëè÷èå îò ïàöèåíòîâ ñ ðåöèäèâèðóþùåé øèçîôðåíèåé çàôèêñèðîâàíî ñíèaeåíèå óðîâíÿ àñïàðòàòà è ïîâûøåíèå óðîâíÿ ãëóòàìèíà â ñûâîðîòêå êðîâè [37]. Ïðåäñòàâëÿþò èíòåðåñ ïðîâåäåííûå â ïîñëåäíåå âðåìÿ èññëåäîâàíèÿ â îòíîøåíèè ñâÿçè ïîâûøåíèÿ äåãðàäàöèè òðèïòîôàíà ñ èçìåíåíèåì öåëîñòíîñòè áåëîãî âåùåñòâà ìîçãà è óðîâíåì ãëóòàìàòà áåëîãî âåùåñòâà ìîçãà ó ïàöèåíòîâ ñ øèçîôðåíèåé.…”
Section: изучение роли аминокислот и ацилкарнитинов в патогенезе шизоunclassified